Bariatric Surgery in Adolescents - Wilson S. Tsai; Thomas H. Inge; Randall S. Burd (2007)
Objectives:To analyze recent nationwide trends in the use of adolescent bariatric surgery and to compare early postoperative outcomes of adolescents and adults undergoing these procedures.Design: Analysis of national administrative data by using survey analysis techniques.Setting: Data obtained from the Nationwide Inpatient Sample from 1996 to 2003.Participants: Adolescents (aged Ͻ20 years) and adults undergoing bariatric surgery.Intervention: